The Learner and Arabic Grammar (A Descriptive Study at the Grammatical Level) - Abdul Aali, Mohamed Al-Mahdi ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2017)
This study investigates the challenges faced by learners in understanding and applying Arabic grammar, with a specific focus on syntactic competence. It highlights the significant weaknesses observed among students, particularly in their ability to apply grammatical rules accurately and appreciate the aesthetic and structural dimensions of the language. The research identifies several contributing factors to this weakness, including student readiness, teacher qualifications, curriculum adequacy, and the nature of assessment tools. Adopting a descriptive approach grounded in classroom observation and professional experience, the study offers practical suggestions aimed at addressing these issues and enhancing learners’ grammatical proficiency. The findings are informed by both scholarly sources and the author's long-standing teaching practice in the field.